Ataque ao feijoeiro (`Phaseolus vulgaris L.) por solitídeos (Coleoptera, Scolytidae): Um grupo novo de pragas potenciais - Pereira Calil, Antonio Cezar; Chandler, Leland (Revista Ceres, 2025)
In the course of crop life table research at Viçosa, Minas Gerais, during the agricultural year 1980/81, to determine the relationships between growing seasons of beans (Phaseolus vulgaris L.) and pest populations, two species of Scolytidae (Coleoptera) were taken as the adults attacked the planted seeds, seedlings and plants in the vegetative to reproductive stages.